Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

Defending pornography: free speech, sex, and the fight for women's rights - Strossen, Nadine (Scribner, 1995)
This book examines a key question that has divided feminists for decades: is censoring pornography good or bad for women? The book makes a powerful case that increasing government power to censor sexual expression, beyond the limits that the First Amendment sensibly permits (for example, outlawing child pornography) would do more harm than good for women and others who have traditionally been marginalized due to sex or gender. The book explains how the very anti-porn laws pushed by some feminists have led to the censorship of LGBTQ+ and feminist works, and it examines the startling connections between anti-porn feminists and right-wing fundamentalists. The book lays out the multiple current assaults on sexual expression, which continue to come from across the ideological spectrum. It shows that freedom for such expression remains an essential prerequisite for the equality, safety, and dignity of women and sexual/gender minorities.
Section: 320 p. : ill. ; 22 cm
Keywords: amériques; cours; discipline; droit; droits des femmes*; liberté d'expression; pornographie; premier cycle; régions géographiques; science politique et droit; sex wars; sex1911; thématiques; états-unis

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques